Bergey's Manual of Systematics of Archaea and Bacteria 2022
DOI: 10.1002/9781118960608.fbm00402
|View full text |Cite
|
Sign up to set email alerts
|

Pirellulaceae

Abstract: Pi.rel.lu.la.ce'ae. N.L. fem. n. Pirellula , type genus of the family; suff. – aceae ending to denote a family; N.L. fem. pl. n. Pirellulaceae the Pirellula family. Planctomycetota / Planctomycetia / Pirellulales / Pirellulaceae The family Pirellulaceae belongs to the order Pirellulales of the class Planctomycetia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Their success in the Ulva microbiome in our IMTA facility could be partly explained due to the high salinity of the Gulf of Aqaba ambient seawater, which is approximately 41% during winter-spring time (Al-Taani et al, 2020 ). While Pirellulaceae ( Planctomycetes phylum) may appear in a broad range of brackish and marine habitats (Lage et al, 2015 ), their high abundance in marine macroalgae is suggested to be due to their ability to degrade sulfated polysaccharides produced by seaweeds and microalgae (Bengtsson and Øvreås, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their success in the Ulva microbiome in our IMTA facility could be partly explained due to the high salinity of the Gulf of Aqaba ambient seawater, which is approximately 41% during winter-spring time (Al-Taani et al, 2020 ). While Pirellulaceae ( Planctomycetes phylum) may appear in a broad range of brackish and marine habitats (Lage et al, 2015 ), their high abundance in marine macroalgae is suggested to be due to their ability to degrade sulfated polysaccharides produced by seaweeds and microalgae (Bengtsson and Øvreås, 2010 ).…”
Section: Discussionmentioning
confidence: 99%